IDENTIFIKASI INFLASI DI KOTA TEGAL DAN ANALISIS PENGENDALIANNYA - Fauziana, Indah; Nusantara, Agung (Jurnal Ilmiah Telaah Manajemen, 2018)
Inflation is an economic condition that indicates a tendency of the general and continuous of price increases. Inflation is the economic benchmark of a country which is related with the people’s purchasing power and macroeconomic stability. The low and stable inflation is a precondition for economic growth that will impact the welfare of society. This study aims to identify the inflation in Tegal City, what commodities are influential and how to control them, using descriptive and analitical methods. Identify and measure the inflation by calculating the deviation standard, from month to month since 2015 until 2017. And so do the same process, to identify what commodities are influential. Based on data analysis, month to month (mtm) the inflation of Tegal City during the period of January 2015 and 2017 showing the highest fluctuation rate compared from the inflation of Central Java and Five cities a cost of living survey in Central Java. This is evidenced by deviation / standard deviation of 0,478 which is the highest than the other cities. Commodity which have the highest fluctuation inflation are a group of foodstuffs derived from the spices sub commodity, namely red chilli , cayenne chilli, and shallot. Inflation control implemented by the Regional Inflation Control Team of Tegal City in general and specifically against the highest fluctuating commodities already done but not yet optimally. Therefore, need a real steps to controlling inflation so the prices become stable and the society was prosperous. Keywords: Inflation Identification, Volatile Foods, TPID, Control Analysis